Poems from Iosif Brodsky’s Cycle From ‘Old English Songs’ as a Rejected Homage to Robert Frost - Соколов, Кирилл; Ботвинова, Екатерина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
The article deals with the history of the creation and publication of poems included in Iosif Brodsky’s cycle From ‘Old English Songs’. The stanzaic features of all four poems suggest that the songs by Robert Burns translated by Samuil Marshak, as well as Robert Frost’s poem “Stopping by Woods on a Snowy Evening” were the most likely sources of the cycle. The second and third poems of Brodsky’s cycle can be considered as a paraphrase of the above-mentioned Frost’s poem. The poem “On the Death of Robert Frost”, which was written at the end of January 1963, elaborates the Frostian context and provides a means of considering the episode as an attempt to master Frost’s poetics. However, neither the paraphrase “Stopping by Woods…” nor the poem in memory of the American poet were ever included in the author’s collections, and the cycle was not fully represented in them. The exclusion of Frost’s episode from the “poetic autobiography” can be explained by the fact that by the time the author’s first collection of poems (1970) was being prepared, the romantic heroism of existential loneliness, which attracted Brodsky to Frost in the early 1960s, had no longer been perceived by him as an invariant of his own fate.